Modern bank management - Norbert Lobo (Chikkamagaluru Selfypage Developers Pvt. Ltd, 2021)
Anytime banking and anywhere banking" is the new truism in the banking sector. Rapid advancements in fields of information technology have resulted in the emergence of new business models, diversified financial products and services and new service delivery channels. Many of these new developments have been duly incorporated in the "Modern Bank Management" course of the B.Com programme.
Keywords: Banking; Investment Policy; Innovative and Digital Banking; Reserve Bank of India